2023
DOI: 10.9734/ijecc/2023/v13i92592
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Peels as Biofertilizers and Biopesticides for Sustainable Agriculture and Horticulture: A Review

Abstract: The annual increase in global population of 1.1% necessitates increased agricultural yields to provide a sustainable food supply, which necessitates the extensive use of chemical fertiliser and pesticide. This practise, however, causes a number of environmental and health issues, which ultimately drives the creation of safer organic fertilisers and bio-pesticides. Organic fertiliser comprises various antioxidants and carbonaceous matter, which are inexpensive and safe elements utilised for plant growth. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The eco-friendliness of biopesticides has been proven by numerous studies. (Devi et al, 2023; Ivase, Nyakuma, Ogenyi, Balogun, & Hassan, 2017) A Study showed that biopesticides had little effect on non-target creatures, protecting beneficial insects and pollinators that are essential to the health of ecosystems. (Giunti et al, 2022) In addition, compared to conventional pesticides, biopesticides have a lower tendency to contaminate groundwater and accumulate permanent residues.…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…The eco-friendliness of biopesticides has been proven by numerous studies. (Devi et al, 2023; Ivase, Nyakuma, Ogenyi, Balogun, & Hassan, 2017) A Study showed that biopesticides had little effect on non-target creatures, protecting beneficial insects and pollinators that are essential to the health of ecosystems. (Giunti et al, 2022) In addition, compared to conventional pesticides, biopesticides have a lower tendency to contaminate groundwater and accumulate permanent residues.…”
Section: Environmental Dimensionmentioning
confidence: 99%